Thermo-mechanical strengthening mechanisms in a stable nanocrystalline binary alloy – A combined experimental and modeling study. (5th February 2019) - Kale, C.; Turnage, S.; Garg, P.; Adlakha, I.; Srinivasan, S.; Hornbuckle, B.C.; Darling, K.; Solanki, K.N.
Abstract: An immiscible nanocrystalline (NC) copper-tantalum (Cu-Ta) alloy is shown to exhibit a stable microstructure under thermo-mechanical loading conditions with exceptional mechanical strength (i.e., 1200 MPa strength at 298 K) indicating anomalous deformation mechanisms as compared to microstructurally unstable nanocrystalline materials. Therefore, in this work, various aspects of strength partitioning in such NC Cu-Ta alloys are discussed and the role of tantalum nanoclusters on the dominant deformation mechanism is presented as a function of temperature. Toward this, initially, the mechanical responses of NC Cu-Ta alloy were measured under uniaxial compression experiments at various temperatures. Later, atomistic simulations were performed along with the high-resolution electron microscopy to identify and validate the rate limiting mechanism behind the plastic deformation in NC Cu-Ta alloys. In general, the observed trend through experiments and simulations identify a transition from a dislocation – nanocluster interaction mediated deformation mechanism to one controlled by grain boundary strengthening as the temperature increases. The former mechanism is shown here to have a crucial role in the observed strengthening behavior of microstructurally stable NC materials. Overall, the paper demonstrates that through effective nano-engineering techniques, it is expected to extend the scope of nanocrystalline materials to a number of engineering design applications. Graphical abstract: Unlabelled Image Highlights: Nanocrystalline (NC) Cu-Ta alloy exhibits superior stability and high temperature strength compared to other NC materials. Grain boundary mediated dislocations interacting with nanocluster govern majority of the strength exhibited by the alloy. Kinetic stabilization of the microstructure aids in the development of advanced NC materials for extreme applications.